The Impact of Workplace Discipline, Placement, and Environmental Conditions on Employee Performance at the East Medan Pratama Tax Services Office - Lubis, M.Tareh Khaifis; Veriana; Putra, Hendardi Gama; Pasaribu, Arie Febiansyah; Safrida; Yusrita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This exploration plans to determine the impact of work discipline, arrangement, and workplace to some extent and, at the same time, representative execution at the East Medan Pratama Duty Administration Office. The exploration was led at the Medan Timur Pratama Expense Administration Office, Jalan Sukamulia Number 17A, Medan City, North Sumatra Region, postal code 20193, with a population of 95 individuals and an examination test of 93 individuals. Information assortment was completed through meetings, polls, and documentation. Using version 24 of the IMB Statistics for Product and Service Solution (SPSS) computer program, multiple regression analysis was used to analyze the data. Given the consequences of the examination, it was found that work discipline significantly affected the presentation of the representatives of the East Medan Pratama Expense Administration Office. This was upheld by the consequences of the examination of t count > t-table (5.984 > 1.987) at n = 93 at an importance level of 95%. The situation meaningfully affects the exhibition of the workers of the East Medan Pratama Duty Administration Office; this is upheld by the investigation of t count > t-table (3.092 > 1.987) at n = 93 at an importance level of 95%. The workplace affects the presentation of the representatives of the East Medan Pratama Expense Administration Office; this is upheld by the determined t < t-table examination (0.569 < 1.987) at n = 93 with an importance level of 95%. The worth of F-count > F table (26.165 > 2.71) expresses that together (different) there is a positive and huge impact of work discipline, situation, and workplace on the presentation of representatives of the East Medan Pratama Expense Administration Office.